An effervescence‐assisted dispersive liquid–liquid micro‐extraction of captopril based on hydrophobic deep eutectic solvent. Issue 11 (23rd August 2021) - Saedi, Hamide; Fat'hi, Mohammad Reza; Zargar, Behrooz
Abstract: In this paper, effervescence‐assisted dispersive liquid–liquid microextraction (EADLLME), based on hydrophobic deep eutectic solvent (HDES) was developed as a green, simple, fast, and sensitive method for the extraction and preconcentration of captopril (CAP) from tablet and urine samples, followed by UV–Vis spectrophotometry. Initially, acetic acid was added to the green extraction solvent (HDES) at μL‐level. This mixture was then transferred by a syringe into bicarbonate fortified sample (contains complex of Ni [II] with CAP); an effervescence reaction occurred immediately between the acetic acid (AA) and sodium bicarbonate. The produced CO2 bubbles led to the dispersion of HDES into the sample. The resulting fine droplets from extractant dispersion facilitated the phase separation. After that, the absorbance of upper phase (HDES rich phase) was measured at 340 nm. Under optimized conditions, we achieved a desirable linearity in the range of 0.07–30 μg/L and low limits of detection of 0.04 μg/L. This developed method was successfully applied for the analysis of tablet and urine samples. Abstract : The HDES was synthesized from Aliquat 336 as hydrogen bond acceptor and β‐CD as hydrogen bond donor has significant properties, such as low volatility, wide liquid range, low vapor pressure, and nontoxicity. The in situ produced CO2 bubbles resulting from the reaction between acetic acid and NaHCO3 was used as a disperser to disperse the extraction solvent (HDES).